Estimated prevalence of Echinococcus multilocularis in rac-coon dogs Nyctereutes procyonoides in northern Branden-burg, Germany - Sabine SCHWARZ, Astrid SUTOR, Christoph STAUBACH, Roswitha MATTIS, Kirsten TACKMANN, Franz Josef CONRATHS (Current Zoology, 2011)
Human alveolar echinococcosis, caused by the larval stage of the small fox tapeworm, is a lethal zoonotic infection if left untreated. E. multilocularis is distributed in the Northern Hemisphere and lives in the small intestines of carnivores, mainly canids. The main definitive host of E. multilocularis in European countries is the red fox (Vulpes vulpes) and in the last ten years new endemic areas for the parasite in Central Europe have been identified. In some areas, for instance in Germany, the raccoon dog (Nyctereutes procyonoides) - a spreading neozoon - must be regarded as an additional definitive host for E. multilocularis. In 2001 this parasite was found for the first time in raccoon dogs in the Federal State of Brandenburg, Germany. Between 2000 and 2008, 1,252 raccoon dogs from Brandenburg were examined by the Intestinal Scraping Technique. The majority of samples were obtained in five northern counties and all 60 animals that tested positive for E. multilocularis were located there. The estimated true prevalence calculated by a beta-binomial- model ranged from 6%–12% [Current Zoology 57 (5): 655–661, 2011].